2010
DOI: 10.2118/118948-pa
|View full text |Cite
|
Sign up to set email alerts
|

Field Applications of Waterflood Optimization via Optimal Rate Control With Smart Wells

Abstract: Summary Waterflood optimization by means of rate control is receiving considerable attention because of increasing deployments of smart well completions and i-field technology. The use of inflow control valves (ICVs) allows us to optimize the production/injection rates of various segments along the wellbore, thereby maximizing sweep efficiency and delaying water breakthrough. Field-scale rate-optimization problems, however, involve highly complex reservoir models, production and facility constra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…Specially, taking equation (11) integral in the direction of well, the Laplace solution of a vertical well is given by…”
Section: The Mathematical Model Of Fluid Unsteady Flow Through Low Pementioning
confidence: 99%
See 1 more Smart Citation
“…Specially, taking equation (11) integral in the direction of well, the Laplace solution of a vertical well is given by…”
Section: The Mathematical Model Of Fluid Unsteady Flow Through Low Pementioning
confidence: 99%
“…[7][8][9] Because of the higher seepage resistance and non-Darcy flow, the sweep efficiency of water flooding is low. 10,11 The advanced water injection method is an effective technology to improve the sweep efficiency and oil recovery. The water is injected into the formation before the producers begin to operate, and a new equilibrium state of higher formation pressure is formed.…”
Section: Introductionmentioning
confidence: 99%
“…They found that closedloop feedback control yields positive gains in NPV for the majority of reservoir behaviors investigated, and higher gains than the open-loop strategy since closed-loop control can also yield positive gains in NPV even when the reservoir does not behave as expected. Datta-Gupta et al (2010) proposed an approach that is computationally efficient and suitable for large field scale. They used streamlines to analytically compute the sensitivity of the arrival times with respect to well rates.…”
Section: Intelligent Well Production Optimizationmentioning
confidence: 99%
“…The variable ' i t is the calculated front arrival time (or time of flight) at production well i, and the desired arrival time t d is given by the arithmetic average of ' i t over all Np wells during each optimization iteration (Alhuthali et al 2010). The vector q contains the control variables and has a dimension of Np.…”
Section: A122 Rate Optimizationmentioning
confidence: 99%